Systematic Literature Review: Implementation of Green Chemistry in Science Education - Al Miza Ginting; Kun Sri Budiasih (Jurnal Pendidikan Kimia Indonesia, 2025)
Green Chemistry in learning is important for fostering students' understanding of the impact of chemicals on the environment and encouraging concern for sustainability. This research uses the Systematic Literature Review method of articles from ScienceDirect, ERIC, and ProQuest (2020-2025) with the keyword “Green Chemistry Education”. The objectives are to identify emerging Green Chemistry principles, integrated chemistry fields, and their implementation in education. The findings reveal three aspects.  First, the most frequently applied principle was Principle 1 (waste prevention). Second, commonly integrated chemistry fields include organic, analytical, basic, polymer, and environmental chemistry, as well as stoichiometry and redox, along with industrial contexts that may serve as case studies in education. Third, the implementation of Green Chemistry was carried out through Project-Based Learning, Problem-Based Learning, active learning strategies (e.g., jigsaw and concept mapping), ethnochemistry, miniature laboratory activities, environmentally friendly practicums, digital escape rooms, and the development of Green Chemistry-based modules and textbooks.